Perspectives on the sharing economy - Wruk, Dominika; Oberg, Achim; Maurer, Indre (Cambridge Scholars Publishing, 2019)
Sharing instead of owning is one of the major trends in modern (business) life. By changing how people consume, the rise of the sharing economy has the potential to redefine the role of owners, consumers and producers, change their mode of transaction, create innovative business models, disrupt existing industries, and challenge political and regulative institutions. In addition to these practical implications, the sharing economy phenomenon represents a novel playground for theoretical advancement, attracting a multitude of research and researchers from different disciplines.